Acceleration of Mechanistic Investigation of Plant Secondary Metabolism Based on Computational Chemistry - Sato, Hajime; Saito, Kazuki; Yamazaki, Mami (Frontiers in Plant Science, 2019)
This review describes the application of computational chemistry to the plant secondary metabolism, focusing on the biosynthetic mechanisms of terpene/terpenoid, alkaloid, flavonoid, and lignin as representative examples. Through these biosynthetic studies, we exhibit several computational methods, including DFT calculations, theozyme calculation, docking simulation, MD simulation, and QM/MM calculation. This review demonstrates how modern computational chemistry can be employed as an effective tool for revealing biosynthetic mechanisms, and the potential of computational chemistry; for example, for elucidating how enzymes regulate regio- and stereoselectivity, finding the key catalytic residue of an enzyme, and assessing the viability of hypothetical pathways. Further, insights for the next research objective involving application of computational chemistry to the plant secondary metabolism are provided herein. This review will be helpful for plant scientists who are not well-versed with computational chemistry.